Folate and Iron deficiencies in Georgia - Tsiklaur, Robizon; Parvanta, I.; Jijeishvili, L.; Kazakhashvili, N. (Caucasus Journal of Health Sciences and Public Health, 2019)
The goal of this paper is to present the results of one nutrition status study in pregnant women carried out in Georgia in. Until 2015, systematic statistical data on micronutrient deficiency was not available in Georgia, to provide developing national strategy. Afterword, in collaboration with the USA CDChas been launched the project “Strengthening surveillance of micronutrient deficiency in Georgia” (grant # 5U2GGH001658). The results of 2 years study show that Iron and folate deficiency was quite common during the1st trimester of pregnancy. Our findings is a “key information for actions” for the public health policy makers to take relevant decisions on required interventions, such as health education, distribution of relevant supplements, and food fortification. Folate and Iron deficiency problems in pregnant is somehow reflection of the general situation existing in Georgia. According to experts opinion it is the quite sufficient evidences for final conclusion and recommendations for the initiation of nutrition interventions.